Religione e politica in Italia: i nuovi sviluppi - Franco Garelli (Quaderni di Sociologia, 2014)
Among the many relevant issues evoked by public discussion on the relationship between religion and politics in Italy, the paper focuses on two of many. The first concerns the possibility of applying the concept of “civil religion” to Italy, implying the presence of a set of shared values, able to offer a sense of unity to the population and strengthen the sense of collective belonging. The second theme concerns the relationship between Catholic Church and politics, a recurring theme in the Italian context and that – while taking on new forms – continues to reflect the particular situation of the country in which the Catholic background and culture are still widespread.